Implementasi Konsep Taman Baca Dalam Redesain Interior Perpustakaan Umum Sebagai Sarana Edukasi Dan Rekreasi Di Kota Surabaya - Rebecca Phylicia Subagio; Diana Thamrin; Anik Rakhmawati (Intra, 2018)
Public library is a public facility provided by the government to educate society in literacy through reading. In fact, literacy rating and reading interest of many people is relatively low, especially in Surabaya. The unattractive interior library becomes one of the causes of those issues. The purpose of this library design is to emphasize the recreational function of a library. Besides increasing people reading interest, a new library design can be a place for people relieving and relaxing. The design methods adapt three stages of design thinking: inspiration, ideation, and implementation. The first stage, inspiration (emphasize, observe and POV), is a basic method that employs emphatic-design approach, where designer acts as a library user, looking at the problems from user’s point of view. The Ideation stage (ideate, prototype, test, and research) is the stage for the design development. The final stage, implementation, is the final execution of the design in various media and platforms. The design result is a public library as ‘reading park’, which incorporate natural elements into the interior space and make the library as a fun place to visit. Therefore, the public library can run it function as educational and recreational facilities, and increase the reading and literacy interest in society.